A study of the key determinants affecting hotel innovation strategic alliances in Cambodia utilizing a structural equation modelling - Charman, Kenneth Paul; Lim, Siphat (Edelweiss Applied Science and Technology, 2025)
Seven latent variables were integrated into Structural Equation Modeling to investigate the effect of Communication, Learning Intent, Mutual Commitment, Trust, Absorptive Capacity, and Knowledge Sharing on Innovation in Cambodia’s four- and five-star hotel industry. A Confirmatory Factor Analysis was adopted to evaluate the model's suitability. The empirical results of this research found that there was a direct positive significant effect of Communication, Mutual Commitment, and Trust on Knowledge Sharing. All latent variables—Communication, Learning Intent, Mutual Commitment, Trust, Absorptive Capacity, and Knowledge Sharing—in this study had a significant positive influence on Innovation. Despite Learning Intent and Absorptive Capacity latent constructs having an insignificant direct effect on the Knowledge Sharing variable, they turned out to have a highly statistically significant impact at the 1 percent level on the Innovation construct through the mediation of Knowledge Sharing. Regarding the estimated path coefficients generated from the model of this research, Knowledge Sharing produced the highest parameter, 3.094, and had a highly statistically significant effect on Innovation, which concluded that the greater the Knowledge Sharing, the more Innovation would be achieved. The second variable that had a substantial direct positive impact on Innovation was Communication, as the estimated slope parameter was 2.738.